2021
DOI: 10.1080/07853890.2021.1898674
|View full text |Cite
|
Sign up to set email alerts
|

DEAH-box polypeptide 32 promotes hepatocellular carcinoma progression via activating the β-catenin pathway

Abstract: Purpose Hepatocellular carcinoma (HCC) is refractory cancer with high morbidity and high mortality. DEAH-box polypeptide 32 (DHX32) was upregulated in several types of malignancies and predicted poor prognosis. Herein, we investigated the role of DHX32 in HCC progression. Methods The expression of DHX32, β-catenin, and epithelial-mesenchymal transition (EMT)-related makers were determined by Western blot and quantitative real-time PCR assays. Cell proliferation was test… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…As a result, early HCC is difficult to diagnose, and the 5-year overall survival (OS) rate is just 34–50% ( Lang et al, 2007 ). Although early HCC can be curable by resection, liver transplantation, or ablation, most patients suffer from an unresectable disease, and there remain no beneficial complete curable ways for HCC patients ( Hu et al, 2021 ). Many studies have revealed that molecular pathological subtypes and driver gene mutations significantly affect the prognosis of HCC patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, early HCC is difficult to diagnose, and the 5-year overall survival (OS) rate is just 34–50% ( Lang et al, 2007 ). Although early HCC can be curable by resection, liver transplantation, or ablation, most patients suffer from an unresectable disease, and there remain no beneficial complete curable ways for HCC patients ( Hu et al, 2021 ). Many studies have revealed that molecular pathological subtypes and driver gene mutations significantly affect the prognosis of HCC patients.…”
Section: Introductionmentioning
confidence: 99%
“…transplantation, or ablation, most patients suffer from an unresectable disease, and there remain no beneficial complete curable ways for HCC patients (Hu et al, 2021). Many studies have revealed that molecular pathological subtypes and driver gene mutations significantly affect the prognosis of HCC patients.…”
mentioning
confidence: 99%
“…Phase clinical trials have found that sirolimus will not improve the long-term recurrence-free survival (RFS) rate of liver transplantation in HCC patients for more than 5 years, but the advantages are significant in the first 3-5 years (142). DEAH-box polypeptide 32, PFK118-310, PFK115-584, and CGP049090 all act on the Wnt/b-Catenin pathway to treat HCC, but there is no clinical trial available to date (143,144). Combination therapy plays an important role in the treatment of HCC.…”
Section: Hcc Treatmentmentioning
confidence: 99%
“…Globally, hepatocellular carcinoma (HCC) is the most prevalent liver cancer type, and the third most important cause of tumor-associated mortality ( Shi et al, 2021a ; Dai et al, 2021 ; Hu et al, 2021 ). However, as a result of local recurrence and metastasis following therapy, most HCC patients exhibit limited benefits and poor outcomes ( Hu et al, 2021 ). Thus, it is vital to evaluate the pathomechanisms that contribute to HCC progression and to establish prognostic biomarkers and treatment targets.…”
Section: Introductionmentioning
confidence: 99%